Peran Pendidikan Islam Dalam Menanamkan Nilai Nilai Moral dan Etika Pada Generasi Milenial - Fauziah, Fara; Putri, Nia Kartika; G, Gusmaneli (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Islamic education plays a crucial role in shaping the character and morality of the millennial generation amid the increasingly complex dynamics of the modern era. This article explores how Islamic education serves as a fundamental foundation in instilling moral and ethical values deeply rooted in the teachings of the Qur’an and Sunnah. Through a thorough learning process, millennials are equipped with an understanding of creed , Islamic law , and ethics , enabling them to internalize noble values such as honesty, responsibility, patience, and tolerance in their daily lives. Furthermore, Islamic education provides essential preparation to face various moral challenges in the digital age, including the negative influences of social media and technology. With innovative learning approaches and synergy among families, schools, and communities, Islamic education contributes to forming millennials who are integrous, responsible, and ready to make positive contributions to society. This article emphasizes that strengthening Islamic education is vital to nurturing a young generation that excels not only intellectually but also possesses strong morals and ethics.